Appréciation de la qualité physiquo-chimique et microbiologique des différents laits (vache, brebis) de la ferme expérimentale L’université de Mostaganem - Boukhatem, Nabil; Ketrouci, Abdel Madjid (My University, 2021)
Milk is considered an equilibrate and complete aliment the reason being its richness in many nutritional elements (proteins, lipids, mineral salts, lactosesand vitamins), to evaluate the particularities and characteristics of the milk of two species (cow and sheep), the objectives of this study centers around these points : the appreciation of the hygienic qualities of the different raw milks (cow and sheep) and the estimation of the microbial flora at the experimental farm at the university of Mostaganem. The physico-chemical analyzes carried out focused on the pH, density, fat and dry matter on the one hand, and on the other hand the microbiological analyzes (the search for: FTAM, total and fecal coliforms, staphylococcus aureus, clostridium sulfite-reducing agent, lactic acid bacteria, yeasts and molds). this research had been carried out in the period of May - June 2021. the results of the study showed that the two types of milk (cow and sheep) are of hygienically acceptable quality with some proliferation of fermentation microorganisms, without pathogenic risks. Microbial loads of FTAM that do not exceed the standards required by the Algerian official journal, and the absence of fecal coliforms indicate good microbiological quality of the samples. And for the physicochemical parameter show a titratable acidity higher than the standards estimated at averages (16.63; 16.50 ° D) for the samples (cow and sheep) respectively, on the other hand a good physicochemical quality is noted for all the other criteria. studied, a density with respective means of (1.030; 1.036). From a nutritional standpoint, the figures have shown that sheep's milk represents the greater load than cow's milk. However, the lipid fraction represents a fat value (29.53 g / l), the total dry extract (156.68 g / l).